PENGARUH KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Sulastiningsih Sulastiningsih; Rizka Imanita Sholihati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
This study aims to determine whether the financial performance measured by using CAR, ROA, LDR, BOPO, and CSR can affect the value of banking companies as measured by using PBV. This study uses secondary data taken from the annual report of banking companies during the year 2012-2016 listed on the Indonesia Stock Exchange. The number of samples of this study as many as 25 banking companies with a total of 125 data. This research method is quantitative research. The results of this study indicate the effect of CAR, ROA, LDR, BOPO, and CSR variables on firm value measured by using PBV in a banking company listed on the Indonesia Stock Exchange.